2021
DOI: 10.1177/15593258211001255
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-873-5p Acts as a Potential Novel Biomarker and Promotes Cervical Cancer Progression by Regulating ZEB1 via Notch Signaling Pathway

Abstract: Objective: Our group aimed to investigate the expression pattern of miRNA-873-5p in cervical cancer (CC) patients and its association with CC progression. Methods: Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was applied for the examination of the expressions of miRNA-873-5p in both CC specimens and cell lines. The clinical significance of miRNA-873-5p was statistically analyzed. MTT, colony formation, Transwell and flow cytometry assays were used to detect cell proliferation, metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…We found that HPV-positive CC individuals with high serum miR-106a expression showed poor prognosis and short overall survival, in accord with the trend of miR-106a-3p in CC [41]. There is evidence suggesting that aberrant miRNA expression is correlated with tumor size, advanced tumor stage, lymph node metastasis, and FIGO stage in CC [42,43]. miR-106a is involved in cisplatin resistance of CC cells [44], and in HPV-induced CC, miR-106a is engaged in the tumorigenesis and is probably a potential candidate element for the diagnosis and prognosis [31].…”
Section: Discussionsupporting
confidence: 78%
“…We found that HPV-positive CC individuals with high serum miR-106a expression showed poor prognosis and short overall survival, in accord with the trend of miR-106a-3p in CC [41]. There is evidence suggesting that aberrant miRNA expression is correlated with tumor size, advanced tumor stage, lymph node metastasis, and FIGO stage in CC [42,43]. miR-106a is involved in cisplatin resistance of CC cells [44], and in HPV-induced CC, miR-106a is engaged in the tumorigenesis and is probably a potential candidate element for the diagnosis and prognosis [31].…”
Section: Discussionsupporting
confidence: 78%
“…Diferent studies have been conducted in order to discover RNA-based cancer biomarkers. Wen et al [6] introduced miRNA-873-5p as a potential biomarker and promising therapeutic approach for CC in their research. Cao et al [7] reported CCAT2 as a candidate biomarker for diagnosing and prognostic predicting CC.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have been done in order to discover RNA-based cancer biomarkers. Chen-Xia Wen et al [6] introduced miRNA-873-5p as a potential biomarker and promising therapeutic approach for CC in their research. Xiaoli Cao et al [7] reported CCAT2 as a candidate biomarker for diagnosing and prognostic predicting CC.…”
Section: Introductionmentioning
confidence: 99%